Tidally driven sulfidic conditions in Peruvian mangrove sediments - Pérez A. (2018)
The seasonal influence of tidal regimes on sulfidic conditions was studied in intertidal environments from a mangrove estuary in Northern Peru. Along two sampling stations, creek water and sediment cores were collected during the dry and wet seasons at all tidal phases (ebb, low, flow, and high tides). Physical-chemical parameters were measured in the creek water (temperature, salinity, pH, Eh, and DO), whereas pH, redox potential (Eh), and total organic matter contents were obtained from the sediment cores. In addition, total dissolved sulfide content ∑ (H2S, HS−, H2−) was measured from sediment pore water. During the dry and wet seasons, the creek water pH, Eh, and dissolved oxygen were lowest in low tide, whereas oxygenated conditions and higher pH and Eh values prevailed in high tide. The total organic matter content in sediments was higher during the dry season, with the highest contents observed in the seaward station. Higher average ∑H2S (landward station, 243.1 ± 234.9 μM L−1; seaward station, 544.9 ± 174.4 μM L−1) were noted during wet season compared to dry season (landward station, 5.3 ± 4.5 μM L−1; seaward station, 430.2 ± 435.1 μM L−1). These ∑H2S contents increased towards the bottom of the sediment column, reflecting the anaerobic decomposition of the organic matter and sulfate reduction. This study provides insight to the geochemical dynamics of intertidal mangrove sediments that are sensitive to fluctuating reducing and sulfidic conditions, oscillating at time scales of minutes to hours.